MODEL PENGELOLAAN PROGRAM PENGALAMAN LAPANGAN PROGRAM STUDI GURU SEKOLAH DASAR FKIP UMS - Muhroji Muhroji Muhroji; Catur Budi Setyanto (Profesi Pendidikan Dasar, 2014)
The purposes of this study are threefolds: a. Describe the management of PPL of PGSDFKIP-UMS conducted so far. b. Formulate the management of model PGSD FKIP PPLUMSin accordance with the demands of competence. c. Describe the policies that shouldbe done so that the PPL management of PGSD FKIP-UMS match with the needs ofstakeholders. The type of the research is qualitative research with design phenomenology.The experiment is conducted in the Faculty of Teacher trainning of UMS, School of partners/where PPL isconducted and associated institutions. The sources of the data are in theform of guidelines for the implementation of PGSD PPL and PPL documents and resourceactivities. The data collection techniques using the techniques of documentation,observation, and interviews as well as a forum group discussion (FGD). The data areanalyzed critically. Critical analysis is conducted are a flow includes the steps of datareduction, data display and conclusion. The validity of the data is done by triangulation ofmethods and sources and do forum group discussion (FGD). The results of the study canbe stated as follows : 1. PPL PGSD management : a. implemented by the managementunit of PPL, b. PPL management of model of FKIP PGSD-UMS can be broadly groupedinto two, namely : 1). PPL programmed, and 2). PPL independent. c. PPL program isintended for regular students, implemented in semester VII, and PPL Independent of PSKGJfor students/students who have become teachers, implemented according to the needs. d.PPL in the curriculum of PGSD FKIP-UMS is an integral part in preparing the prospectivestudents as professional teachers. e. PPL PGSD FKIP-UMS is more emphasied onthe practice of schooling and learning practices. 2. PPL PGSD model was promoted “ModelPengelolaan Terpadu/Kolaboratif”, PGSD FKIP-UMS relationship with partner schoolnot only in implement PPL stage. But since PGSD Curriculum development, implementationPPL to reporting stage. 3. policies that should be done PGSD FKIP-UMS are : a. Ithas “Laboratorium School”; b. PPL financing should include comprehensive activities;c. election partner school with more emphasis on teacher competence oficials than schoolacreditation.